An exploratory study on the impact of social inclusion-based public library transformation program on sustainable development in West Sumatera - Rahmah, Elva; Winoto, Yunus; Shuhidan, Shamila Mohamed; Marlini; Erlianti, Gustina; Asmara, Rini; Triska, Yona (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2025)
Background of the study: One of the important roles of libraries is to build a knowledge-based society ecosystem by making libraries an open interaction space through a library transformation strategy based on social inclusion. Purpose: The study was designed to investigate the issues associated with retooling and re-skilling cataloguing librarians in the digital era. Method: The design used is a qualitative analysis based on a detailed case study of the impact of the Social Inclusion-Based Library Transformation Program on Community Welfare in West Sumatra, Indonesia. Findings: The core impact of the Social Inclusion-Based Library Transformation Program is summarized by five objectives: enhancing access to information (via digitalization/literacy), fostering community skills development (via targeted training), reducing unemployment rates (via job skills/entrepreneurship), promoting social participation (via community engagement), and improving the local economy (via business development/creative economy). Conclusion: Through the programs implemented, libraries can strengthen their role as public libraries in improving the quality of human resources, so that community literacy skills increase, enabling them to play a more active role in sustainable development and achieving the goals set out in the SDGs.